EFFECT OF HOME VISIT ON HOSPITAL READMISSION - ES Hajikazemi; K Falahat; S Assemi; F Hosseini (Iran University of Medical Sciences, 2002)
Background : Heart failure is a chronic disease with relapsing nature. As a result the recurrent hospitalization of patient with heart failure has become a major topic of discussion in the field of health care. Various studies has shown that home visit exert a positive influence on readmission and mortality rate in these patients.   Objective : To determine the effect of home visit on readmission rate in patients with cardiac failure.   Design : This was a field trial with control group. Three home visits were carried out in the cases but not in the control group over a six-ninth period. At the end, the number of admission in the two group were compared.   Samples : 100 patients diagnosed with heart failure were enrolled by continuous sampling into the study and then distributed into 50 cases and 50 controls.   Results : Result indicated that the case group experienced fewer readmission during the 6month period of the study than the control group the difference being statistically significant [z=2.096and p= 0.044]. Hospital stay was also shorter in cases than in controls, the difference again being statistically significant [t=20.39 and p= 0.017].   Discussion : The result showed that home visit lead to a reduction in rehospitalization rates in patients with heart failure. Therefore, it is recommended that regular, systematic home visit can lessen complications and prevent deterioration of the disease, thereby reducing re-admission rates in these patients.